2017
DOI: 10.1038/s41598-017-07611-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of lncRNA H19 and LIPCAR are associated with increased risk of coronary artery disease in a Chinese population

Abstract: Recent studies in animal models and humans show that long non-coding RNAs (lncRNAs) are involved in the development of atherosclerosis, which contributes to the pathological foundation of coronary artery disease (CAD). LncRNAs in plasma and serum have been considered as promising novel biomarkers for diagnosis and prognosis of cardiovascular diseases, especially CAD. We here measured the circulating levels of 8 individual lncRNAs which are known to be relevant to atherosclerosis in the plasma samples from 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 37 publications
1
115
1
Order By: Relevance
“…Long non-coding RNA H19 was significantly upregulated in the serum of patients with atherosclerosis and those with a high risk of coronary artery disease in a Chinese population (125,126). In addition, H19 was also induced by ox-LDL and inhibition of H19 protected HUVECs and HAVSMCs against ox-LDL induced apoptosis via sponging miR-148b or miR-let-7, respectively (88,89).…”
Section: H19mentioning
confidence: 99%
“…Long non-coding RNA H19 was significantly upregulated in the serum of patients with atherosclerosis and those with a high risk of coronary artery disease in a Chinese population (125,126). In addition, H19 was also induced by ox-LDL and inhibition of H19 protected HUVECs and HAVSMCs against ox-LDL induced apoptosis via sponging miR-148b or miR-let-7, respectively (88,89).…”
Section: H19mentioning
confidence: 99%
“…In recent decades, lncRNAs acquire recognition for their importance in a variety of biological processes, including growth, differentiation, pluripotency, embryonic development, homeostasis, and disease. 18 Furthermore, emerging evidence has suggested that lncRNAs played an important role in hypoxia via regulating hypoxic gene expression at transcriptional, and posttranscriptional, and translation levels. 14,15 For example, lncRNA BACE1-AS was upregulated in heart failure, 16 plasma lncRNA UCA1 expression was associated with poor prognosis in chronic heart failure patients 17 and lncRNA H19 expression was associated with increased risk of coronary artery disease.…”
mentioning
confidence: 99%
“…A growing number of recent studies display that lncRNAs play pivotal roles in diverse physiological and pathological processes in the cardiovascular system. For example, increased plasma levels of lncRNA H19 and LIPCAR are associated with increased risk of CAD . A study reports that long intergenic noncoding RNA 00305 sponges miR‐136 to regulate the hypoxia‐induced apoptosis of human umbilical vein endothelial cells .…”
Section: Discussionmentioning
confidence: 99%